Improving Forage Production Quantity and Quality Using Native Legume Species in Semi-arid Agrosilvopastoral System - Louhaichi, Mounir; Slim, Slim; Gamoun, Mouldi; Hassan, Sawsan; Jamel, Kailene; Hamdeni, Imtinene (Kenya Agricultural and Livestock Research Organization, 2022)
Agrosilvopastoral systems provide a range of livelihood services, either directly through forage production or indirectly by the beneficial effects on soil conservation, nutrient cycling, pollutant filtering, and biodiversity enhancement. Hence, improved silvopastoral systems have ample scope to rehabilitate degraded pastures to sustain livestock production, which remains a strong pillar for the livelihoods of the agrosilvopastoral communities. To evaluate the impact of Hedysarum coronarium L. (sulla) reseeding on pasture productivity, plant cover and plant density in semi-arid silvopastoral systems, an experiment was carried out in Sbaihia Site, Zaghouan Governorate, Tunisia during 2018-2019 growing season. The experiment was laid out under a randomized complete block design having 3 treatments including reseeding sulla; protection from grazing and control (free grazing) with three replications per treatment. Preliminary results showed that there were significant differences (p<0.05) among the three treatments. Reseeded sulla and protected plots recorded 100% plant cover while the control plots had less than 60%. The estimated biomass for the reseeded plots was four times higher than the biomass production in the protected plots and eleven times higher than the control plots. The highest plant density was recorded in the reseeded plots (163.2 plants/m2), followed by the protected plots (30.6 plants/m2) while the lowest value was recorded in the control plots (29.8 plants/m2). Based on these findings, it is concluded that reseeding well-adapted native forage species has a great potential to improve productivity of semiarid silvopastoral systems, which would contribute towards reducing the feeding cost and, therefore, enhancing the income of the agrosilvopastoral communities